Projeto de controlador gain scheduling usando realimentação derivativa via LMI - Hardy Llins, Lázaro Ismael [UNESP] (2015)
In this thesis are presented results for the stability of linear time-varying systems (Linear Parameter Varying - LPV). At first, it is described a method for designing a gain scheduling controller via linear matrix inequalities (Linear Matrix Inequalitites - LMIs), based on the stability theory of Lyapunov with time-variant parameter and using state derivative feedback. It is proposed a method to design a gain scheduling controller using state derivative feedback and also considering parametric uncertains. This new formulation was manipulated using the lemma of Finsler, and allowed to find the control law without having to invert a symbolic matrix